The Determinants of Muslim Millennials' Intention Towards Savings Sukuk - Rajut Prasetya; Syifa Fauziah; Arief Bowo Prayoga Kasmo (AL-MUZARA'AH, 2022)
Savings Sukuk is one of the sharia investment products issued by the Indonesian Government. Investors from the millennials generation always dominate Savings Sukuk sales, although it is a new investment instrument in Indonesia. Therefore, we interest in examining the intention towards Savings Sukuk more deeply. In particular, this study analyzes the effect of religiosity, product knowledge, and pricing on Muslim millennials' intention toward Savings Sukuk in Indonesia. This study used a quantitative approach, and the data collected was analyzed by Partial Least Square – Structural Equation Modeling (PLS-SEM). Purposive sampling was used to get the required sample. Respondents in this study were Muslim millennials in Indonesia and were not limited by region. There are at least 138 respondents who participated in the survey. The results showed that product knowledge and pricing influenced Muslim millennials' intention toward Savings Sukuk. In contrast, religiosity does not affect Muslim millennials' intention toward Savings Sukuk in Indonesia.